Comparative studies on milk parameters and somatic cell count of Badri cattle over Sahiwal and crossbred counterparts - THAKUR, SWATI; HUOZHA, R; DHARA, S; MAITI, A; RASTOGI, S K (The Indian Journal of Animal Sciences, 2023)
This study aims to provide reference values of some of milk parameters and somatic cell count of Badri cows as well their comparison with Sahiwal and crossbred counterparts. Lower milk SCC in Badri cattle reflects their resistance to mastitis. Further, the use of milk SCC as a management tool on a routine basis will help to maximize immunity and improve quality and quantity of milk as well as cattle’s comfort and welfare. In India, higher milk production was never the reason for reversing Zebu/indigenous germplasmas quality of milk has been the talk of folklore. The data generated provides only meagre baseline information on comparison studies on milk composition of Badri, Sahiwal and crossbred cattle. Additional studies are required to substantiate the results.